Dinamika Komunikasi Mitigasi Bencana Kebakaran Hutan Dan Lahan Pemerintah Dan Masyarakat - Fatan Audi Havip; Susie Perbawasari; Agus Rahmat (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
Forest and land fires (Karhutla) have received great attention because of their large impact on the environment. Fire contributes to deforestation rates, habitat loss & species extinction, as well as greenhouse gas emissions. Jambi is the smallest province of the provinces in Sumatra which is a land and forest fire-prone area compared to the provinces of Riau and South Sumatra. This study examines the dynamics of karhutla disaster mitigation communication between the government and the community in Muaro Jambi district, Jambi Province, which is the district with the most high level of karhutla. Through the use of a constructivist paradigm, this study is expected to uncover the dynamics of communication between the government and community karhutla disasters that occur in Jambi Province and how these dynamics cause forest and land fires in Jambi which occur every year. The results of this study found the dynamics of communication between the government and the government, the government and the community, and the community and the community in mitigating karhutla disasters in Jambi Province.